Ectomycorrhizal fungal communities of Quercus liaotungensis along local slopes in the temperate oak forests on the Loess Plateau, China. Issue 2 (10th January 2013) - Zhang, Jian; Taniguchi, Takeshi; Tateno, Ryunosuke; Xu, Ming; Du, Sheng; Liu, Guo‐Bin; Yamanaka, Norikazu
Abstract: Topographic factors strongly affect the diversity of plants and local environmental conditions, yet little is known about their effects on the distribution of ectomycorrhizal fungi (EMF). By combining morphological and molecular identification methods, we investigated the relationship between EMF communities of Quercus liaotungensis and topographic factors along local slopes in the temperate oak forest on the Loess Plateau of northwest China. ITS‐RFLP analysis revealed a high diversity of EMF taxa (135 taxa) associated with Q. liaotungensis along three local slopes. EMF communities among slope sites or slope positions, tended to share major common EMF species, which accounted for more than 80 % of the total EMF abundance, and showed a diverse distribution, which mainly related to rare species. Ordination analyses showed that EMF taxa distribution was significantly correlated with several environmental variables (slope site, slope position, slope gradient, and soil C:N). Topography‐mediated changes of environmental conditions may be important determinants of the distribution of EMF taxa along local slopes (slope position and slope site) in the central Loess Plateau.